THE ANALYSIS OF THE EXISTING OF MINIMARKET TOWARD THE SUSTAINABILITY OF PEDDLING IN BATU LAYAR AND GUNUNGSARI DISTRICT WEST LOMBOK - Lalu Takdir Jumaidi Jalaludin M. Akhyar - (IQTISHADUNA, 2018)
The aims of this research are (1) to know the perception of shop retailers and peddlers toward the existing of modern mart, (2) to know its’ impact toward peddlers, (3) to know the implementation of government’s rule about modern mart, and (4) to know the efforts of shop retailer and peddlers to survive.It is descriptive-exploratory research. Variables used are modern mart, shop retailers, and peddlers. Population gathered from shop retailers and peddlers in Batu Layar and Gunungsari. 30 of them are taken as sample. Data gathered through interview, questionnaire, and documentation. Data analyzed using percentage, mean, and ideal mean. Qualitative method followed reduction data, display, and conclusion drawing.Result shows that (1) the implementation of governments’ rule on modern mart is not running well, (2) high negative perception of shop retailers and peddlers toward modern mart, (3) negative impact of modern mart toward shop retailers’ and peddlers’ turnover (32% and 29%), income (30% and 17.5%), and customers (32% and 29%), and there is minimum effort for sustainability by shop retailers and peddlers.